Microbes and Parkinson's disease: from associations to mechanisms. Issue 8 (August 2022) - Cannon, Tyler; Gruenheid, Samantha
Abstract : Parkinson's disease (PD) is a neurodegenerative disorder influenced by both genetic and environmental factors. The mechanisms leading to neurodegeneration in PD are still under investigation, with several mechanistic models currently proposed. A number of microorganisms have been associated with increased risk of PD in humans, and recent research using newly developed models has begun to elucidate how these microbes may factor into disease development. Newly identified roles for PD-associated genes in host–microbe interactions and response to infections have also recently been uncovered, providing further evidence for microbial contributions to PD. Here we summarize these recent advances in the field and discuss them in the context of both historical and emerging hypotheses for PD development, with a particular focus on the application of rodent models as systems allowing for mechanistic hypothesis testing. Highlights: Several microbes, including viruses, bacteria, and fungi, have been associated with an increased risk of PD in humans. Microbial infections can induce similar common pathways that are associated with PD, including systemic inflammatory responses, α-synuclein misfolding, and disruption of mitochondria. PD-associated gene mutations can impact host–microbe interactions, suggesting that even familial forms of PD may be influenced by microbes. New models have recently been developed which allow for mechanistic investigations of microbial contributions to PD development. Although not confirmed, epidemiological evidence from past pandemics has raised concerns over the potential for SARS-CoV-2 to promote PD.